China-US economic rivalry: implications for Southeast Asia - Gao, Jacque (2023)
The China-US rivalry, which shows no signs of abating, has both economic and political implications for Southeast Asia. This commentary explains the economic and political impact of the rivalry on the countries of Southeast Asia and the choices the region faces in this new age of great power competition.